2020
DOI: 10.3390/cells9112423
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Metabolic Dissection of ATRA-Induced Granulocytic Differentiation in NB4 Acute Promyelocytic Leukemia Cells

Abstract: Acute promyelocytic leukemia (APL) is a hematological disease characterized by a balanced reciprocal translocation that leads to the synthesis of the oncogenic fusion protein PML-RARα. APL is mainly managed by a differentiation therapy based on the administration of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). However, therapy resistance, differentiation syndrome, and relapses require the development of new low-toxicity therapies based on the induction of blasts differentiation. In keeping with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…Subsequently, we determined the time-frame of the perturbations caused by ATRA on CRLS1/LPGAT1/LPCAT1/LPCAT2/LPCAT4/LCLAT1 and PGS1. Thus, we compared our RNA-seq data with the publicly available transcriptomic results obtained in NB4 cells exposed to ATRA for 4, 12, 24, 72, and 120 h [ 34 , 35 ] (Fig. 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we determined the time-frame of the perturbations caused by ATRA on CRLS1/LPGAT1/LPCAT1/LPCAT2/LPCAT4/LCLAT1 and PGS1. Thus, we compared our RNA-seq data with the publicly available transcriptomic results obtained in NB4 cells exposed to ATRA for 4, 12, 24, 72, and 120 h [ 34 , 35 ] (Fig. 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties and configuration of the ECM have been demonstrated to play important roles in sustaining proliferation, evading growth suppression, resisting cell death, enabling replicative immortality, inducing angiogenesis, activating invasion, avoiding immune destruction, deregulating cellular energetics, and facilitating genomic instability and tumor-promoting chronic inflammation 17 . Numerous interactions between esophageal cancer cells and the ECM seem to be intricate 18 . Many studies have demonstrated that different ECM molecules play a regulatory role in the development and metastasis of ESCC 19 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Albanesi and colleagues [20] found that ATRA treatment, a differentiation therapy, in the acute promyelocytic leukemia cell line NB4, correlates with the activation of aerobic glycolysis and the reduction in OXPHOS-dependent ATP production, proposing that granulocytic differentiation and patient therapy could be favored by OXPHOS inhibition. A tight association between current cancer therapies and metabolic rewiring was also proposed by Verma and colleagues [21].…”
Section: Synopsismentioning
confidence: 99%